Emergency Department–Based Human Immunodeficiency Virus Preexposure Prophylaxis Referral Program—Using Emergency Departments as a Portal for Preexposure Prophylaxis Services. Issue 8 (August 2021) - Zhao, Zezhou; Jones, Joyce; Arrington-Sanders, Renata; Gladfelter, Gaby; McDonald, Steven; Reed, Christopher; Myer, Deanna; Schlenker, Noah; Fulton, Glenn; Jones, Tiana; Saheed, Mustapha; Rothman, Richard; et al.
Abstract : Abstract: A pilot program was implemented to assess the feasibility of emergency department (ED) preexposure prophylaxis (PrEP) referral. Of 119 eligible patients approached and assessed, 39 (33%) expressed interest and were referred to peer navigators. Of these, 16 (41%) scheduled for appointments; four (10%) initiated PrEP, which demonstrated ED-based PrEP referral was feasible. Abstract : Supplemental digital content is available in the text.An emergency department–based preexposure prophylaxis referral program integrated into an established human immunodeficiency virus screening program is feasible and acceptable and could serve as an important portal for preexposure prophylaxis service.